Guardians of republicanism the Valori family in the Florentine Renaissance - Jurdjevic, Mark (Oxford University Press, 2008)
This work examines the relationship between the Valori family and the political and intellectual evolution of the Florentine Renaissance. Following the family's fortunes over five generations, Jurdjevic retraces its involvement in the political struggles that marked this turbulent period in the history of Florence.